Rediscovery of two species of Neoperla (Plecoptera: Perlidae) from China - Mo, Raorao; Liu, Ruijun; Li, Weihai; Shi, Mingwang (Zootaxa, 2020)
Two species of the perlid genus Neoperla of the montivaga species group, N. longispina Wu, 1938 and N. minor Chu, 1929, are redescribed from Hainan and Zhejiang provinces of China, respectively. Neotypes are designated for both taxa. Illustrations and color photographs are provided for each species. Their taxonomic relationships are discussed with related congeners.